Spatial Variability of Nutrients and Chlorophyll-A as Contributing Factors of Trophic Condition in Kendari Bay, Southeast Sulawesi - Rahayu, Siti Mira; Azzahra, Mutiah; Irawan, Hendra; Salwiyah, Salwiyah; Sari, Iya Purnama; Alsita, Indah; Bramana, Aditya; Maulita, Mira (Jurnal Kelautan Tropis, 2025)
Estuaries and coastal waters are heavily influenced by anthropogenic activities and environmental factors, which can lead to ecosystem degradation, increased nutrients, and the risk of eutrophication. Kendari Bay, with its complex hydrodynamic conditions and various human activities in the vicinity, requires an analysis of the distribution of nutrients and chlorophyll-a (chl-a) to estimate the potential for eutrophication and its impact on aquatic ecosystems. This research was conducted in March-May 2023 at six stations in Kendari Bay. The distribution of nutrients in Kendari Bay revealed a varied pattern, with DIN concentrations higher in the “neck area” or narrow parts of the bay, phosphates more concentrated in the inner part due to slow water flow, and silica more abundant in estuaries because it comes from weathering rocks carried by river flows. Chl-a concentration tended to correspond DIN pattern, suggesting that phytoplankton growth was more influenced by nitrogen nutrients than phosphorus nutrients, as supported by an N:P ratio of less than 16. Overall, Kendari Bay was classified as mesotrophic with a relatively uniform trophic level due to morphological and hydrodynamic characteristics that narrow towards the sea and a low flushing rate. A comprehensive approach to managing human activities from upstream to downstream must be performed effectively to protect the bay area from eutrophication and environmental decline due to excessive nutrient runoff from land-based activities.